PANDAWARA AS A MODEL OF YOUNG GENERATION PARTICIPATION IN ENVIRONMENTAL ISSUES - Anggaranta Sajidan Keliat; Marsya Adwa Nadzifa; Quina Malkha; Mazaya Zatalini; Siti Rahmadani Lubis (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
This study aims to analyze the existence of Pandawara Group in influencing the participation of the younger generation in environmental issues. This study also aims to invite the community to do greening. Thus we can maintain our sustainability by building a community group to maintain the sustainability of nature in Indonesia, and most importantly reduce the use of hanging plastic waste. One of the causes of flooding in every part of Indonesia, and around 36.50% of flooding in Indonesia is caused by garbage that clogs every river in every river in Indonesia, thus inhibiting the flow of river water to the beach or ocean. And in this study we will discuss one by one.